THE VALIDITY OF MARRIAGE AGREEMENT DEEDS MADE BY NOTARIES FOR INTERFAITH COUPLES - Dinda Putri Sugiarto; Ajeng Aditya Listyani (Authentica: Private Law Journal, 2025)
Notaries have the authority to draw up authentic deeds which are very important in assisting the public, especially in the preparation of deeds such as marriage agreements. A marriage agreement, made by the prospective husband and wife, serves to regulate aspects related to marriage and has strong legal force. In Indonesia, the phenomenon of interfaith marriage often occurs, although Law Number 1 of 1974 has not explicitly regulated this matter. The Problem Formulation is regarding how the validity of a marriage agreement made by a notary for interfaith couples is and how the validity of a marriage agreement made abroad for interfaith couples is, with the aim of analyzing the validity of marriage agreements made by notaries for interfaith couples as well as marriage agreements made abroad. The research method used is normative legal research by collecting primary and secondary data. The research results indicate that the validity of a marriage agreement made by a notary for an interfaith couple depends on the fulfillment of legal requirements and not contradicting religious provisions. In addition, the validity of marriage agreements made abroad is also influenced by registration requirements and the authority of ratification. This study concludes the need for clearer regulations regarding interfaith marriages and better education for notaries to handle such cases